Efficacy Evaluation of Aspirin Plus Prednisone or Prednisolone in IVF/RIF Patients: A Systematic Review and Meta-Analysis - Yanyan Tang; Xin Tong (IMR Press, 2024)
Background: We conducted a comprehensive systematic review and meta-analysis to evaluate the diverse impacts of combining aspirin with prednisone or prednisolone on patients undergoing in vitro fertilization (IVF) or experiencing recurrent implantation failure (RIF). Our analysis encompassed parameters such as clinical pregnancy rate, implantation rate, live birth rate, miscarriage rate, and fertilization rate. Our primary objective was to resolve the debate regarding the comparative efficacy of prednisone versus prednisolone when administered alongside aspirin in women undergoing assisted reproduction. Methods: A variety of electronic databases were searched between 1984 and December 2023, including PubMed, Web of Science, Embase, the China National Knowledge Infrastructure (CNKI), the China Biology Medicine Disc (CBM), and the CQVIP Database. We employed the Newcastle-Ottawa Scale and the Cochrane Risk of Bias Tool for the quality evaluation. We used Stata 12.0 and Revman 5.4 to pool the data. Results: In this meta-analysis, 10 trials, including 2902 individuals, were considered. Aspirin plus prednisone or prednisolone might improve clinical pregnancy rates (relative risk (RR) = 1.13; 95% confidence interval (95% CI) = 1.03-1.23) and implantation rates (RR = 1.27; 95% CI = 1.01-1.60) compared with the placebo or no treatment group. Conclusions: Our findings suggest that aspirin plus prednisone or prednisolone may improve clinical pregnancy rates and implantation rates in patients with IVF or RIF, and in the subgroup of ANA-positive patients, it may also improve implantation rates. Further design of larger randomized controlled trials is required to determine whether aspirin in combination with prednisone or prednisolone may improve assisted reproductive outcomes in patients undergoing IVF or RIF, considering the limits of study enrollment.